Impact of Momordica Charantia (Karela) on the Body Weight in the Streptozotocin-Induced Diabetic Rat - Mohal, Shirin; Mondal, DK; Shamim, KM (Bangladesh Journal of Anatomy, 2013)
DOI: http://dx.doi.org/10.3329/bja.v9i2.15282 Bangladesh Journal of Anatomy 2011 Vol.9(2) pp.106-109